Dialectical-Relational Approach on Profanity Words among Muslim Students - Wiraatmaja, Triastama; Sabgini, Kharisma Naidi Warnanda (Celt: A Journal of Culture, English Language Teaching & Literature, 2024)
Speaking in good manner is highly advised in Islamic teaching, but this notion had been challenged by socio-cultural values of the kinds if profanity words circulating among Muslim students. As qualitative research, this research aimed to investigate the discourses related to the use of profanity words among Muslim students from the perspective of the Dialectical-Relational Approach (DRA). The first was to discover the most frequent profanity words uttered by Muslim students, the reasons for using profanity words which were classified as propositional and non-propositional, and how DRA perceived the use of profanity words influenced their identity as Muslim. In this research, a questionnaire was chosen as the primary instrument, which consisted of a set of profanity words by Chirs Kirk, and the respondents’ reasoning for using profanity words. The respondents were 14 students from a private Islamic-based university in Indonesia. The result had shown that the students chose two profanity words as the most popular: shit and fuck. Meanwhile, the most dominant reason for using profanity words was to relieve tension which belonged to the non-propositional aspect. DRA perceived the complexity of profanity words among Muslim students and  the use of profanity words emphasized the socio-cultural aspect of language, yet, Islamic teaching encouraged the use of good-mannered utterances because it might alter people’s opinion about Islam negatively. Thus, the researchers perceived the use of profanity words as a complex phenomenon that encompasses various contexts.